Pemanfaatan Limbah Padi dan Tebu Menjadi Briket dan Pupuk Silika Cair di Desa Suling Wetan, Bondowoso - Sundahri; Hasanah, Hepniatul; Widyaningsih, Windi; Sianipar, Novika Aliza; Hendriana, Fezira Rosa; Ayumasita, Karomitafitri; Gunawan, Vito Chandra; Rahman, Difany Aulia; Jazimah, Hilda Nurwakidah; Qodriyati, Zainatul (Universitas Mataram, 2023)
Waste problems are still a phenomenon today, especially in the people of Suling Wetan Village, Cermee District, Bondowoso District. The village of Suling Wetan is one of the villages where most of the people have livelihoods as farmers with a total land area of around 650 ha. In one harvest will produce 5-6 tons of rice and 4 tons of sugar cane which will produce 8 kw of waste, if multiplied by the land area will produce 520 tons of waste in one rice and sugar cane harvest. Almost all agricultural waste produced is thrown away without treatment. This research aims to utilize agricultural waste, especially rice and sugar cane into briquettes and liquid silica fertilizers that have a sale value and added value. The informant of this study was the village community of Suling Wetan, especially the peasant group. The research began by making observations, socializing and continuing at training sessions on how to make briquettes and liquid silica fertilizer and doing mini demos. The manufacture of briquettes and silica fertilizers has the same main ingredients namely rice waste and sugar cane with tapioca flour support ingredients for briquette charcoal, detergent for silica fertilizer, and water. Making briquette charcoal has different treatments for charcoal powder, different treatments can produce different textures and qualities. Likewise with the application of silica fertilizer, silica will affect plants if the application concentrates on 100% silica. Waste treatment not only affects the environment, but can also be used to add economic value.